Modern aspects on etiopathogenesis of canine osteoarthritis - DANOURDIS (Α. Μ. ΔΑΝΟΥΡΔΗΣ) A. M; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
Extracellular matrix and chondrocytes are the main structure components of the articular cartilage. The extracellular matrix is largely comprised of collagen fibers, proteoglycans and water, whereas the metabolically active chondrocytes are responsible for its production and maintenance. An interaction of the physical and biochemical characteristics of the articular cartilage is necessary for normal joint function by providing nearly frictionless motion, wear resistance, joint congruence and loading transmission to subchondral bone. The vicious cycle of osteoarthritis sets forth when structural and homeostatic aberrations, secondary to congenital or acquired joint diseases, occur in the articular cartilage. Although the pathological and biochemical changes of the articular cartilage in the osteoarthritic joint have been studied extensively, the exact mechanism pertaining its pathogenesis is still unknown.